Quantitative characterization and analysis of pore-fractures in tar-rich coal under high-temperature pyrolysis based on micro-CT imaging - Yang, Fu; Jiang, Pengfei; Duan, Zhonghui; Cheng, Zhongyan; Wang, Zhendong (Frontiers in Earth Science, 2023)
This study investigates pore distribution and permeability behavior of tar-rich coal following high-temperature pyrolysis at 500°C using X-ray computed tomography (CT) scanning. Coal samples post-pyrolysis were CT scanned, generating 1755 cross-sectional slices for three-dimensional reconstruction. An axial algorithm extracted pore distribution features, and geometric parameters were computed. An Equivalent Pore Network Model analyzed permeability characteristics. The results show that Post-pyrolysis pore distribution in tar-rich coal exhibited nonuniformity with a significant range in pore size distribution. Pores displayed concentrated spatial patterns. Total porosity was 14.24%, with 12.34% being connected. Most pores in Representative Elementary Volume (REV) regions fell within 10–50 μm in width and 20–60 μm in length, constituting over 40% of the total. Pore surface area peaked between 200–100 μm2, also comprising over 40% of the total. The Pore Network Model showed distinct characteristics in two REV regions: REV-1 demonstrated an early stage of development with poor connectivity, while REV-2 displayed a well-developed network with a bimodal coordination number histogram. The study highlights nonuniform post-pyrolysis pore distribution and significant pore size variations in tar-rich coal. This study is crucial for understanding permeability behavior in tar-rich coal after high-temperature pyrolysis.